A Review on Design and Stress Analysis of Tail Cone Rotary Agitator in Horizontal Feeder: Design and Analysis of a Tail Cone Rotary Agitator for Pulp Feeding in Horizontal Feeders (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The proposed work of a cone hub stirring device in pulp feeding, the work proposed will be carried out for validation and anti-deflection solutions. It is a horizontal heavy work application to generate pulp feeding and horizontally screening in order to prevent height inlet feeding. This chaos operation is distinct from traditional methods of those in vertical position. The tail cone agitator has been designed to satisfy the application for this application finish. The results show that all built parameters can withstand the given limits. Boundary requirements to be determined often provide rotary parameters for pulp capability and vessel volume. Pulp is the medium in which this method is used, pulp is basic wood bleaching from a hot bleaching preheater and all these machineries form part of the paper and pulping industry as the feeder to a screw conveyors method. Gusseting rings for optimum stability and thickness of the covering board. To reduce the weight of the entire cone structure. The wide frame, which would form within the cone, was so well intended to be shaped. The results show the comparison with validation for stress analysis and deflection analysis in multiple built tail cone agitators as well as demonstrate stability with modal analysis.